2020
DOI: 10.3389/fonc.2020.564779
|View full text |Cite
|
Sign up to set email alerts
|

Trimodal Therapy vs. Radical Cystectomy for Muscle-Invasive Bladder Cancer: A Meta-Analysis

Abstract: Background: To compare the difference between trimodal therapy (TMT) and radical cystectomy (RC) in treating muscle-invasive bladder cancer, we performed a meta-analysis for data from the following database. Methods: We searched PubMed, Chinese biomedicine literature database, the Cochrane Library, China National Knowledge Internet databases, Wanfang databases, and Google Scholar up to December 2019. The main outcome measures assessed were overall survival (OS), cancer-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
5
0
7
Order By: Relevance
“…In a setting of a multidisciplinary bladder cancer clinic, authors observed that TMT provided midterm survival outcomes comparable to RC in a propensity score sample [ 9 ]. A meta-analysis based on 8 clinical studies totally observed a statistically significant difference at more than 10-year OS between RC and TMT, with relatively higher OS and DSS and lower mortality rate for MIBC patients who underwent RC compared to TMT [ 26 ]. Authors also observed that based on 5 studies with follow-up time more than 10 years, RC was superior to TMT regardless of OS or DSS rates [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a setting of a multidisciplinary bladder cancer clinic, authors observed that TMT provided midterm survival outcomes comparable to RC in a propensity score sample [ 9 ]. A meta-analysis based on 8 clinical studies totally observed a statistically significant difference at more than 10-year OS between RC and TMT, with relatively higher OS and DSS and lower mortality rate for MIBC patients who underwent RC compared to TMT [ 26 ]. Authors also observed that based on 5 studies with follow-up time more than 10 years, RC was superior to TMT regardless of OS or DSS rates [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis based on 8 clinical studies totally observed a statistically significant difference at more than 10-year OS between RC and TMT, with relatively higher OS and DSS and lower mortality rate for MIBC patients who underwent RC compared to TMT [ 26 ]. Authors also observed that based on 5 studies with follow-up time more than 10 years, RC was superior to TMT regardless of OS or DSS rates [ 26 ]. By contrast, another meta-analysis reported that TMT generated outstanding 5-year OS rates among these two interventions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy coupled with chemotherapy and tumor transurethral resection (bladder-sparing trimodality therapy) has emerged as a radiation-based bladder sparing treatment for localized disease, showing comparable survival outcomes with radical cystectomy [ 7 , 8 ]. Selectively increasing bladder tumor sensitivity to radiation could improve the efficacy of this treatment, limiting its side effects and reducing the need for cystectomy.…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время не опубликованы результаты длительных рандомизированных исследований сравнения РЦЭ и ТМТ. Имеющиеся данные указывают на отсутствие существенных различий в основных онкологических показателях, особенно в случае реализации протоколов ТМТ в условиях специализированных учреждений [18][19][20][21].…”
unclassified
“…Преимущество РЦЭ подтверждает и анализ КСВ (ОР 1,34; 95 % ДИ 1,18-1,54; р <0,0001). Авторы сделали вывод о том, что предполагаемая продолжительность жизни <10 лет является дополнительным фактором в пользу выбора ТМТ [20]. Схожие результаты получены в исследовании A. Kumar и соавт.…”
unclassified